Methodology for estimating the dependence between force and deformation – a vehicle crash case - Mijailović, Radomir M. (Journal of Applied Engineering Science, 2012)
Accident reconstruction software analyzed impact of vehicles considers usage of coefficient of restitution as a known quantity. In practice it is common that numerical value of coefficient of restitution is determined on basis of experience. Presence of error in its evaluation causes an essential error in output results. Thus, it is of exceptional importance to determine more precisely its numerical value. Improved solution of vehicle accident reconstruction software is presented in this paper. To archive that, in this paper was developed methodology which provides such analysis of impact process in which the coefficient of restitution becomes the result, and not input data. We have suggested new methodology for mathematical modeling of function dependence between force and deformation in a collision of vehicles. The compression process was approximated with piecewise linear function. The restitution process was approximated with linear curves. During process of restitution stiffness depends on maximum value of deformations during process of compression. The quality of the coherence between experimental data and mathematical function is quantified by residual sum of squares. Numerical examples are performed by usage of the obtained methodology.